Changes in the textural quality of selected cheese types as a result of frozen storage - Herald, T. J.; Schmidt, Karen A. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
The change in textural quality of cheese during frozen storage is of concern to the frozen food industry. Many food products such as frozen pizza and dinner entrees are stored at !0.5EF or below for extended periods of time. Food manufacturers have noted detrimental changes including reduced elasticity of cheese on pizza or the absence of melt in filled products. Dynamic rheological testing was used to determine the changes in Cheddar, Colby, and Mozzarella cheeses during frozen storage. Slices of cheese were tested at day 0 and after 30 days of storage at !0.5EF. Elastic attributes were measured at 40, 70, and 194EF. Results indicated that frozen storage reduced the elastic properties of all three cheeses. When cheeses were subjected to higher temperatures, the elastic properties decreased. These changes could be attributed to proteolysis, chemical composition, and component interactivity. Dynamic testing is rapid and may be a method of choice for cheese manufacturers to determine shelf life and quality.
Keywords: Dairy; Dairy products; Cheese; Melting properties; Frozen storage